Rapid techniques for DNA extraction from routinely processed archival tissue for use in PCR. Issue 4 (April 1994) - Sepp, R; Szabó, I; Uda, H; Sakamoto, H
Abstract : AIMS--To evaluate the ability of four rapid DNA extraction methods to provide DNA for the polymerase chain reaction (PCR) from routinely fixed, paraffin wax embedded archival tissues. METHODS--Eighteen blocks of various tissues, 18 blocks of cervical cancer specimens, and nine blocks of B cell lymphomas were investigated. Both normal and biopsy specimen sized tissues were studied. DNA was extracted using four methods: boiling for 20 minutes in distilled water; boiling for 20 minutes in 5% Chelex-100 resin solution; 3-hour proteinase K digestion; and 3-hour proteinase K digestion, followed by boiling in 5% Chelex-100. Different exons of the p53 gene, human papillomavirus type 16 (HPV 16) sequence, and immunoglobulin heavy chain (IgH) gene rearrangement were amplified from the extracts. RESULTS--The Chelex boiling, proteinase K digestion, and proteinase K digestion-Chelex boiling methods produced DNA suitable for amplification in all of the 45 samples. Boiling in water yielded insufficient template for the PCR in three of the 45 cases (7%), and in six of 42 positive cases (14%) much fainter bands were observed, mostly when the processed material was either biopsy specimen sized or a B cell lymphoma sample. Fragments of the p53 gene were successfully amplified up to 408 base pairs in water boiled extracts, up to 647 in Chelex boiled preparates, and up to 984 in proteinase K digested and proteinase K digested-Chelex boiled samples, although with decreased sensitivity in the last case. All of the templates were reusable after 3 months of storage at -20 degrees C. CONCLUSIONS--Chelex boiling, proteinase K digestion, and proteinase K digestion followed by Chelex boiling produce suitable templates for the PCR from a large variety of paraffin wax embedded tissues. As the simple 20 minute boiling method in 5% Chelex-100 solution requires minimal manipulation and time, it could be useful, especially in the routine processing of large amounts of material.